The psychology of natural history. (December 2022) - Burns, K.C.; Low, Jason
Abstract : Natural history observations are an integral part of ecology and evolution. However, they can be underappreciated because they operate independent of the scientific method. Here, we illustrate that the science of natural history has its own methodology based on a well-known psychological paradigm that describes how the human mind learns.